The impact of mandatory helmet use on career length in the national hockey league (nhl). Issue 11 (25th May 2017) - Reinsberger, Claus; Frick, Bernd
Abstract : Objective: In 1979, the National Hockey League (NHL) announced that helmets would become mandatory for incoming players. The objective of this study is to evaluate, whether the mandatory use of helmets has a positive impact on the career length in NHL players. Design: A public database (www.hockeydb.com) was utilised to extract career lengths of NHL players before and after 1979. Since the rule allowed players who signed professional contracts prior to June 1, 1979 to continue not to wear a helmet, career lengths of all players entering the NHL via the draft in ten seasons before (1969–1978) and ten seasons after (1979–1988) the introduction of the helmet rule was compared. Main results: In the 20 years analysed, 3952 players were selected by NHL teams of which 1818 eventually appeared in at least one match and were considered for further analysis. Controlling for draft round, draft number, individual players' performance (games played per season, number of goals and assists per game, number of penalty minutes per game), year of entry and team picking the player, players during the era of mandatory helmet use had significantly longer careers (approximately 2.5 years, cox regression z=−0.768, p<0.01). Defenders and forwards benefit to the same extent from wearing a helmet. Conclusions: The introduction of mandatory use of helmets in the NHL was associated with an increase in career length. Protection of head and brain together with associated conditions may be contributing to this observation. Competing interests: None.